Functional study of a KCNH2 mutant: Novel insights on the pathogenesis of the LQT2 syndrome. Issue 9 (30th July 2019) - De Zio, Roberta; Gerbino, Andrea; Forleo, Cinzia; Pepe, Martino; Milano, Serena; Favale, Stefano; Procino, Giuseppe; Svelto, Maria; Carmosino, Monica
Abstract: The K + voltage‐gated channel subfamily H member 2 (KCNH2) transports the rapid component of the cardiac delayed rectifying K + current. The aim of this study was to characterize the biophysical properties of a C‐terminus‐truncated KCNH2 channel, G1006fs/49 causing long QT syndrome type II in heterozygous members of an Italian family. Mutant carriers underwent clinical workup, including 12‐lead electrocardiogram, transthoracic echocardiography and 24‐hour ECG recording. Electrophysiological experiments compared the biophysical properties of G1006fs/49 with those of KCNH2 both expressed either as homotetramers or as heterotetramers in HEK293 cells. Major findings of this work are as follows: (a) G1006fs/49 is functional at the plasma membrane even when co‐expressed with KCNH2, (b) G1006fs/49 exerts a dominant‐negative effect on KCNH2 conferring specific biophysical properties to the heterotetrameric channel such as a significant delay in the voltage‐sensitive transition to the open state, faster kinetics of both inactivation and recovery from the inactivation and (c) the activation kinetics of the G1006fs/49 heterotetrameric channels is partially restored by a specific KCNH2 activator. The functional characterization of G1006fs/49 homo/heterotetramers provided crucial findings about the pathogenesis of LQTS type II in the mutant carriers, thus providing a new and potential pharmacological strategy.